Exploring green skills: a study on the implementation of green skills among secondary school students - Kamis, Arasinah; Che Rus, Ridzwan; Rahim, Mohd Bekri; Nur Yunus, Faizal Amin; Zakaria, Normah; Mohd Affandi, Haryanti (Human Resource Management Academic Research Society, 2017)
Green skills are the technical skills, knowledge, values and attitudes needed in the workforce to develop and support sustainable social, economic and environmental outcomes in business, industry and the community (as defined by the Green Skills Agreement, Australia). School teachers play a role in producing skilled labor that has green skills. The aim of this research is to explore the views of teachers regarding the instilling of green skills in students and the types of green skills applicable in schools. This research is a qualitative investigation using the method of in-depth interview to collect information from the teachers who handle the subject of Living Skill Integration in secondary schools. The respondents opine that the school can disseminate preliminary information about green skills, but the application of these skills in real life requires experienced teachers. Furthermore, these skills can be infused into various subjects so that students can have a holistic perspective of sustainability. The respondents also state that the types of skills applicable in schools are recycling or material management, which will minimize the use of electricity and water. The applications of these green skills in schools are a real challenge to teachers, but they will encourage students to commit themselves to the good cause of environment. Therefore, all parties concerned must make a concerted effort to promote green skills so that students and the public are well aware of the importance of preserving the environment.